The Influence Of Career Development And Remuneration On Organizational Commitment With Work Motivation As An Intervening Variable In Nurses At Medika Lestari Hospital - Arif Sebastian; Nofierni Nofierni; Anastina Tahjoo (International Journal of Medicine and Health, 2024)
Organizational commitment throughout the world, especially in Indonesia, is still very low. Similarly, in RS Medika Lestari itself, it can be seen that the commitment of each is not optimal with high nurse turnover and the tenure of nurses, most of whom are less than 1 year. For this reason, this study will examine the factors that are thought to affect organizational commitment, especially in RS Medika Lestari.This study will use factors such as Career Development, Remuneration, and Work Motivation. This research is an explanatory research using a quantitative approach. This study uses a research instrument in the form of a questionnaire distributed to 80 respondents who are nurses at RS Medika Lestari. The results obtained from this study are career development and remuneration partially have a significant influence on organizational commitment and work motivation. Work motivation can mediate the influence between career development on organizational commitment, work motivation also can mediate the influence between remuneration on organizational commitmen.